Effect of whitening mouth rinses on the chemical and physical properties of a nanofilled composite - Laura Carolina Kepler; Ana Paula Morona Rodrigues; Mauro Antonio Dall Agnol; Sinval Adalberto Rodrigues-Junior (Universidade Estadual de Campinas, 2021)
Aim: This study analyzed the effect of whitening mouth rinses on water sorption (WS), solubility (SL), color change, and surface roughness of a nanofilled composite. Whitening perceptibility and acceptability (WID) were also studied. Methods: Forty specimens of Filtek Z350XT, shade EA2 were produced and randomly distributed (n=8) to AS - artificial saliva (control); LWE - Listerine Whitening Extreme; CLW - Colgate Luminous White; LCM - Listerine Cool Mint; and CP - Colgate Plax. They were immersed in the mouth rinses 2x/day, for one minute, during 28 days. The color was assessed using an Easyshade spectrophotometer (CIE-L*a*b* system). Surface roughness (Ra-μm) was measured with three parallel measures, using an RP-200 roughness meter. The WS and SL (μg/mm-3) were analyzed based on the ISO 4049 recommendations. The data were analyzed using one- and two-way ANOVA/Tukey tests (α=0.05). Results: Surface roughness significantly increased after immersion in AS and LCM, with no significant differences between the groups either before or after immersion. The ΔE* was not significantly different between the groups. All substances produced a ΔWID higher than the 50%:50% perceptibility and acceptability thresholds. The WS and SL were not significantly affected by the mouth rinses. Conclusion: Whitening mouth rinses did not affect WS, SL, surface roughness, and color stability of a nanofilled composite, regardless of the presence of ethanol in the composition.